2005
DOI: 10.1159/000083555
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the Location of Carcinoma in situ (CIS) of the Urinary Bladder Using Pirarubicin Hydrochloride

Abstract: Introduction: No established technique for locating solitary carcinoma in situ (CIS) of the urinary bladder or CIS accompanying bladder cancer has been determined. Here we investigated whether the location of CIS of the urinary bladder can be macroscopically ascertained by instilling pirarubicin hydrochloride (THP) into the urinary bladder. Patients and Methods: We dissolved 50 mg of THP in 50 ml of distilled water, and instilled the resulting solution into the urinary bladder. After 5 min, the urinary bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This drug was successfully developed in Japan in 1979 ( 17 ). THP could quickly get into bladder tumor cells, and bladder tissues spread with high selection, little whole-body absorption and relatively high level of safety ( 18 ). Results obtained from other studies ( 19 ) suggested that anthracene ring revealed fluorescence, and THP was quickly absorbed by bladder tumor tissues after bladder pouring, and the drug concentration inside the tumor was 4-fold higher than that in normal bladder tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This drug was successfully developed in Japan in 1979 ( 17 ). THP could quickly get into bladder tumor cells, and bladder tissues spread with high selection, little whole-body absorption and relatively high level of safety ( 18 ). Results obtained from other studies ( 19 ) suggested that anthracene ring revealed fluorescence, and THP was quickly absorbed by bladder tumor tissues after bladder pouring, and the drug concentration inside the tumor was 4-fold higher than that in normal bladder tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, intravesical therapy, which includes intravesical chemotherapy and immunotherapy (1), has become an important part of bladder tumor treatment. The drugs commonly used in intravesical chemotherapy include mitomycin, doxorubicin, epirubicin, and THP (17-20), while the drugs used for intravesical immunotherapy are bacillus Calmette-Guérin vaccines. We selected THP for the present study because its prophylactic effect is greater than that of mitomycin and epirubicin (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of THP uptake for malignant mucosal lesions in our study was 96% and 74.7%, respectively, which is identical to that of previously documented photodynamic diagnosis. 21 Uchikoba and colleagues 14 reported sensitivity and specificity of up to 100% and 97.5%, respectively, using THP for malignant mucosal lesions; however, this difference may be attributed to different samples, diagnostic instruments, and THP dosage and retention time.…”
Section: Discussionmentioning
confidence: 99%
“…THP is pigmented and selectively absorbed by bladder tumor cells. In a preliminary study, Uchikoba and associates 14 reported the utility of intravesical instillation of THP in the macroscopic detection of flat malignant lesions, such as CIS. THP is similar to the color of the bladder mucosa, however, which can make discrimination of targeted cells difficult, especially when bleeding or cystitis is present.…”
Section: Introductionmentioning
confidence: 99%